The independent predictors of non‐alcoholic steatohepatitis and its individual histological features: Insulin resistance, serum uric acid, metabolic syndrome, alanine aminotransferase and serum total cholesterol are a clue to pathogenesis and candidate targets for treatment - Ballestri, Stefano; Nascimbeni, Fabio; Romagnoli, Dante; Lonardo, Amedeo (Hepatology research, 2016)
The diagnosis of non-alcoholic steatohepatitis (NASH) is based on the individual histological features: steatosis, lobular inflammation and ballooning. Non-alcoholic fatty liver disease (NAFLD) activity score (NAS ≥ 5) is used in clinical trials. Fibrosis dictates long-term NAFLD prognosis. Recently, more-than-mild portal inflammation has raised interest as a marker of NAFLD severity. We assessed the independent predictors of: (I) individual histological lesions of NASH; (II) diagnosis of NASH; (III) significant (stage ≥2) and advanced (stage ≥3) fibrosis; and (IV) more-than-mild portal inflammation. Data from 118 consecutive biopsy-proven NAFLD patients observed at our institution were retrospectively analyzed. At stepwise multivariate logistic regression analyses, independent predictors were as follows. For the individual histological features of NASH: insulin resistance (IR), assessed with Homeostasis Model Assessment-IR (HOMA-IR), serum uric acid (SUA) and serum total cholesterol (TCH) for moderate-to-severe steatosis; waist circumference (waist), HOMA-IR and TCH for lobular inflammation; waist, HOMA-IR, metabolic syndrome (MS), serum alanine aminotransferase (ALT), SUA and TCH for ballooning. For NASH diagnosis: waist, HOMA-IR, MS, ALT, SUA and TCH (Brunt et al.'s classification); ALT, SUA and TCH for NAS ≥ 5. For significant and advanced fibrosis, respectively: waist, MS and ALT; age, platelets, HOMA-IR, diabetes and TCH. For more-than-mild portal inflammation: serum aspartate aminotransferase (AST), serum iron, NAS ≥ 5 and significant liver fibrosis. HOMA-IR, SUA, MS, ALT and TCH are independent predictors of NASH and its individual histological lesions, notably including fibrosis. Based on our findings, these factors should be considered major pathogenic drivers of NASH and, by inference, potential targets for treatment.